Instrumentation in Potts Spine: A Two Year Retrospective Study in CCM Medical College and Hospital Durg - Trivedi, Dr. Adarsh (International Journal of Innovative Research in Medical Science, 2018)
Most of the patient suffering from tuberculosis can be managed on anti-tuberculous therapy. Spinal TB patients can present with various signs and symptoms which include leg or back pain, palpable mass in the paraspinal region, kyphotic deformity and neurological compromise, out of these most important sequelae of TB spine are kyphotic deformity and neurological compromise. The spinal cord undergoes intrinsic changes due to tuberculosis and late-onset paraplegia is produced, with consequent poor chances of neural recovery even after surgery. When treatment is started the diseased segment of the spine or vertebral body is the weakest portion and it must be protected by suitable external braces. Fracture and dislocation of a diseased vertebral body may occur secondary to mechanical trauma and surgical decompression adds further instability. So indications for instrumented stabilisation can be advised. Surgical management or instrumentation in Pott’s spine helps regain motor function and ameliorates disability. Material and Methods: 38 patients were included with Thoracic and Thoracolumbar Pott's disease. Included patients were having severe kyphosis with an active disease. Clinical evaluation of the outcome measures were evaluated at baseline, postoperatively and at 3rd, 6th and 1 year. Preoperative and postoperative X-ray, loss of kyphotic correction. Average operation time, bony fusion and implant failure were observed. Results: During study period total 1456 patients were diagnosed as TB out of which 99 were extra pulmonary cases and 58 were diagnosed as pott’s spine with thoracic and thoracolumbar TB and 38 patients were included in the study who meet the inclusion criteria for our study. In our study of the 38 patients 18 were male and 20 were female patients. Mean age was 43.82. In Dorsal group D1 to D4, D5 to D8 and D9 to D12 involvement was seen in 4(10.53%), 10 (26.32%) and 13 (34.21%) respectively. Multi-segment involvement was observed in 3 (7.89%) patients. Dorsolumbar and lumbar involvement was seen in 5 patients. In lumber, L1 to L2, L2 to L3, L3 to L4 and L4 to L5 involvement was 1(2.63%), 0, 1(2.63%) and 2 (5.26%) respectively. Mean operation time was 290±41minutes and mean hospital stay was 16 days ranging from 8 days to 72 days. 34 patients had a successful bony fusion within a mean of 7±1.2 months, whereas 4 patients had late fusion or nonfusion because of secondary infections. Mean preoperative kyphosis was 21 degrees which was corrected to 9 degrees in final follow up after instrumentation. Conclusion: Instrumented stabilisation is safe in spinal TB. Posterior transpedicular approach is a safe surgical procedure for thoracic and thoracolumbar Pott's spine. Also Posterior transpedicular approach shows improved functional status and significantly improves neurological pain and fusion rate. However clinical trials with a larger sample size and a longer follow-up period are required.